2022
DOI: 10.32493/jee.v4i2.17130
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Debt To Asset Ratio Terhadap Return On Asset Pada PT Asuransi Sinar Mas, Tbk Periode Tahun 2011-2020

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh Debt to Asset Ratio terhadap Return On Asset pada PT. Asuransi Sinar Mas, Tbk Periode Tahun 2011-2020. Metode yang digunakan adalah explanatory research. Teknik analisis menggunakan analisis statistik dengan pengujian regresi, korelasi, determinasi dan uji hipotesis. Hasil penelitian ini variabel Debt to Asset Ratio diperoleh nilai rata-rata sebesar 67,68%. Variabel Return On Asset diperoleh nilai rata-rata 1,075%. Debt to Asset Ratio berpengaruh positif dan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This test is used to determine the minimum and maximum scores, the highest scores, rating scores and standard deviations of each variable (Harsanto et al, 2017)Following are the output results from the data that has been processed through the SPSS 25 application, namely: Based on the Descriptive Test Results above, it can be concluded that: a. Financial Literacy Variable (X1), from these data it can be described that the minimum value is 9 while the maximum value is 20 and the average value of Financial Literacy is 17.75.…”
Section: Descriptive Analysis Testmentioning
confidence: 99%
“…This test is used to determine the minimum and maximum scores, the highest scores, rating scores and standard deviations of each variable (Harsanto et al, 2017)Following are the output results from the data that has been processed through the SPSS 25 application, namely: Based on the Descriptive Test Results above, it can be concluded that: a. Financial Literacy Variable (X1), from these data it can be described that the minimum value is 9 while the maximum value is 20 and the average value of Financial Literacy is 17.75.…”
Section: Descriptive Analysis Testmentioning
confidence: 99%